Bacterial community profiling and identification of bacteria with lignin-degrading potential in different gut segments of African palm weevil larvae (Rhynchophorus phoenicis) - Lenka, Jessica; González-Tortuero, Enrique; Kuba, Shweta; Ferry, Natalie (Frontiers in Microbiology, 2025)
The microbiota within the guts of insects plays beneficial roles for their hosts, such as facilitating digestion and extracting energy from their diet. The African palm weevil (APW) lives within and feeds on the high lignin-containing trunk of palm trees; therefore, their guts could harbour a large community of lignin-degrading microbes. In this study, we aimed to explore the bacterial community within the gut of the APW larvae, specifically with respect to the potential for lignin degradation in various gut segments as a first step to determining the viability of mining bacterial lignin-degrading enzymes for the bioconversion of lignocellulosic biomass to biofuels and biomaterials. Bacterial metagenomic DNA was extracted from the foregut, midgut, and hindgut of larvae of the APW, and the V3–V4 hypervariable region of the 16S rRNA gene was sequenced using the Illumina MiSeq platform. The generated data were analysed and taxonomically classified to identify the different bacterial phylotypes within the gut community cumulatively and per gut segment. We then determined the presence, diversity, and abundance of bacteria associated with lignin degradation within each larval gut compartment as a basis for suggesting the gut segment(s) where lignin degradation occurs the most. All sequences were classified and belonged to the bacterial kingdom. Firmicutes (54.3%) and Proteobacteria (42.5%) were the most dominant phyla within the gut, followed distantly by Bacteroidota (1.7%) and Actinobacteriota (1.4%). Enterococcus, Levilactobacillus, Lactococcus, Shimwellia, Megasphaera, Klebsiella, Pectinatus, Salmonella, Lelliotia, and Enterobacter constituted the most abundant genera found across all gut segments. The foregut and midgut had many similar genera, whilst the hindgut appeared unique. Overall, 29.5% of total gut bacteria comprising 21 genera were lignin degraders found predominantly in the Firmicutes and Proteobacteria phyla (56.8 and 39.5%, respectively), then moderately in Actinobacteriota (2.5%) and Bacteroidota (1.1%). The most abundant ligninolytic genera were Levilactobacillus (46.4%), Klebsiella (22.9%), Enterobacter (10.7%), Lactiplantibacillus (5.9%), Citrobacter (2.2%), Corynebacterium (1.8%), Paucilactobacillus (1.8%), Serratia (1.5%), Bacteroides (1.1%), and Leucobacter (1.0%) found in different amounts in different gut compartments. The foregut had the most diverse and highest abundance of lignin-degrading phylotypes, and we present reasons that point to the foregut as the main location for the depolymerization of lignin in the APW larval gut.